Social and physical environmental factors in daily stepping activity in those with chronic stroke. Issue 3 (3rd April 2021) - Miller, Allison; Pohlig, Ryan T.; Reisman, Darcy S.
ABSTRACT: Background, Purpose/Objective: Walking behavior in the chronic stroke population is multi-factorial. Previous work focused on the role of physical and biopsychosocial factors in understanding daily stepping post stroke. However, qualitative evidence suggests that social and physical environmental factors also affect daily stepping in those with stroke. The purpose of this study was to understand the role of social and physical environmental factors in daily stepping after stroke. Methods: A total of 249 individuals ≥6 months post stroke were included in this cross-sectional analysis (129 females, mean age 62.98 years, SD 11.94). The social environment included living situation, work status, and marital status. The physical environment included the Area Deprivation Index (ADI) and Walk Score. At least 3 days of stepping was collected using an accelerometry-based device. Predictors were entered sequentially into a regression model: demographic characteristics, social environmental factors, and physical environmental factors. Results: After adjusting for demographic factors, social environmental factors explained 6.2% ( p =.017) of the variance in post stroke daily stepping. The addition of physical environmental factors improved the model (ΔR 2  =.029, p =.024). The final model explained 9.2% ( p =.003) of the variance in daily stepping. Lower area deprivation (ADI β = −0.178, p =.015) and working (working vs. retired β = −0.187, p = .029 and working vs. unemployed β = −0.227, p =.008) were associated with greater daily stepping. Discussion/Conclusion: Social and physical environmental factors predicted daily stepping and should be considered when setting expectations relative to the effects of rehabilitation on daily stepping in individuals poststroke.